Improvement of Properties of Poly(L-lactic acid) through Solution Blending of Biodegradable Polymers - Johnner Sitompul; Rizky Insyani; Daniel Prasetyo; Hermawan Prajitno; Hyung Woo Lee (Journal of Engineering and Technological Sciences, 2016)
This study concerns the improvement and enhancement of the properties of poly(l-lactic acid) (PLLA) through simple solution blending of pure PLLA with different kinds of biodegradable polymers. Synthesized PLLA was blended with synthesized poly(d,l-lactic acid) (PDLLA) or poly(ethylene glycol) (PEG) at various composition ratios in a solvent mixture of dichloromethane/ethanol at room temperature to produce dipolymer. The polymer-blend properties were analyzed using FTIR, DSC, UTM data and an enzymatic degradation test was conducted. It was found that PLLA blend films were obtained with limitation of the second polymer content up to 20% (w) through solvent casting. From the DSC data, two different melting temperature peaks showed that stereocomplex formation occurred during polymer precipitation for all PLLA/PDLLA blends, while only one single melting temperature peak appeared in the PLLA/PEG blend. Regarding the mechanical properties, the PLLA/PEG blend showed better performance with an improvement of the mechanical strength by around 11.18% and an improvement of the elongation at break by around 89% compared to pure PLLA. Furthermore, after the 48-hour enzymatic biodegradability test, the PLLA/PEG blends showed improvement of biodegradability with 21.88% of sample weight-loss compared to 2.53% for pure PLLA.